VD_FINDINFO Pron / 2012 / 17 vom 24. Januar 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS | 107 al. 1 let. c CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 98 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)